2015
DOI: 10.1016/j.devcel.2014.11.030
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Phosphorylation of CENP-A at Ser68 Orchestrates Its Cell-Cycle-Dependent Deposition at Centromeres

Abstract: The H3 histone variant CENP-A is an epigenetic marker critical for the centromere identity and function. However, the precise regulation of the spatiotemporal deposition and propagation of CENP-A at centromeres during the cell cycle is still poorly understood. Here, we show that CENP-A is phosphorylated at Ser68 during early mitosis by Cdk1. Our results demonstrate that phosphorylation of Ser68 eliminates the binding of CENP-A to the assembly factor HJURP, thus preventing the premature loading of CENP-A to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
109
2
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 93 publications
(120 citation statements)
references
References 47 publications
5
109
2
1
Order By: Relevance
“…Several studies suggested that mitotic cyclins and CDK1/2 kinase activity are inhibitory for ectopic CENP-A loading by mediating phosphorylation of M18BP1, HJURP and the Ser68 residue of CENP-A itself (1820). Cyclin E1 forms a functional kinase complex with CDK2 at the G1/S boundary to regulate cell cycle progression into S phase (36).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies suggested that mitotic cyclins and CDK1/2 kinase activity are inhibitory for ectopic CENP-A loading by mediating phosphorylation of M18BP1, HJURP and the Ser68 residue of CENP-A itself (1820). Cyclin E1 forms a functional kinase complex with CDK2 at the G1/S boundary to regulate cell cycle progression into S phase (36).…”
Section: Resultsmentioning
confidence: 99%
“…4G). A recent study suggested that Cyclin B1/CDK1 phosphorylates CENP-A at Ser68 (20). Depletion of Cyclin E1 or CDK2 by shRNAs had no impact on CENP-A Ser68 phosphorylation levels by western blotting (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The structure of centromeric chromatin undergoes cell cycle-dependent transitions Recently, a number of studies demonstrated that the assembly of CENP-A is temporally regulated by phosphorylation/dephosphorylation of CENP-A at Ser68 (Yu et al 2015), chaperone HJURP , and the "priming" factor Mis18 complex (McKinley and Cheeseman 2014). The tight regulation results in a change of CENP-A in a strictly cell cycle-dependent manner and ensures proper centromere function during mitosis after temporal recruitment of specific kinetochore proteins.…”
Section: Cenp-a Chromatin Displays a Distinct Higher-order Organizationmentioning
confidence: 99%